Classroom Talk: The Ubiquity of Feedback - Monteiro, Vera; Mata, Lourdes; Santos, Natalie; Sanches, Cristina; Gomes, Marta (Frontiers in Education, 2019)
Classroom interactions play an important role in the learning and teaching of mathematics, and feedback emanating from these interactions is a powerful tool for enhancing student learning. These exchanges have been widely studied in higher education, but very few investigations have been carried out at the level of elementary students and teachers. This study aimed to contribute to existing knowledge of feedback, and to formulate guidelines to improve teacher feedback in elementary school. The specific objectives were to analyse the focus of feedback a) by pedagogical moment and type of interaction, b) by type of question and student’s answer, and c) by gender and student achievement. Participants comprised five teachers and their 82 third-grade students attending an elementary school in Portugal. Mathematics lessons were video-recorded and a categorisation system to assess teacher-student interaction was developed, based on a review of the literature and empirical data. The results showed that most of the teacher–student interactions contained feedback, which was usually focused on a specific task, and less frequently on the ways in which tasks were processed. In all pedagogical moments, teachers’ feedback was evaluative, especially when they had initiated the interaction. Feedback became more effective when the initial move was made by the students. The focus of feedback was not related to the type of question asked, but it was associated with the certitude of the students’ answers. We also observed an interaction effect between the focus of feedback, gender and achievement, with high-achievement boys receiving advantages. Our results hold important implications for teachers’ classroom practices and professional development